Down by Law - Müller, Robby 1940-2018; Waits, Tom 1949-; Braschi, Nicoletta 1960-; Benigni, Roberto 1952-; Barkin, Ellen 1954- (<<The>> Criterion Coll., 2002)
A comedy feature about two lowlifes, a small time pimp and an unemployed disc jockey, framed for a crime they didn't commit, who escape from jail with an eccentric Italian tourist. Set in New Orleans and the swamps of Louisiana.
Bildformat: 1.78:1 aspect ratio. - New high-definition digital transfer, enhanced for widescreen television
Orig.: USA 1986
Enth. thoughts and reflections by Jim Jarmusch ; isolated music track ; optional French dub track, featuring Roberto Benigni ; 2002 video interview with director of photography Robby Müller ; 1986 Cannes Film Festival press conference with Jarmusch and stars John Lurie, Roberto Benigni and Nicoletta Braschi ; 1986 John Lurie interview with commentary ; outtakes ; Q & A with Jarmusch ; Jarmusch's phone calls with Waits, Benigni and Lurie ; production polaroids ; location stills
Keywords: Comedy films; Feature films; Fugitives from justice -- Louisiana -- Drama; Flucht; Strafverfolgung; Täter; Louisiana